Evaluation of oral health status and salivary flow rate in obese patients after bariatric surgery - Marsicano, Juliane A; Sales-Peres, Arsenio; Ceneviva, Reginaldo; Sales-Peres, Silvia H de C (European Journal of Dentistry, 2012)
Objectives: The aim of this study was to identify the prevalence of dental caries, periodontal diseases and tooth wear in bariatric patients, and relate the oral health conditions to saliva flow.Methods: Fifty-two patients who had undergone bariatric surgery (Roux-en-Y gastric bypass) and 50 severely obese patients indicated for bariatric surgery were submitted to clinical examinations with regard to dental caries (DMFT index), periodontal condition (CPI index), dental wear (DWI index – Dental wear index) and saliva flow. The data were statistically analyzed by the Student’s-t , Mann- Whitney, Spearman Correlation and Chi-square (χ2) tests at 5% significance level.Results: The DMFT index was 16.11±5.19 in the surgical group and 16.06±6.29 in the control group (P>.05). The mean CPI was 3.05±0.84 for the operated group and 2.66±1.25 for the obese patients with no significant difference between them (P>.05). There was statistically significant difference between the groups for the presence of periodontal pockets (P=.021). All the patients presented some degree of tooth wear, however, with no significant difference between the two groups (P=.82). The mean saliva flow values of the surgical group and control group were 0.64±0.46 mL/min and 0.66±0.49 mL/min, respectively. There was no significant difference in saliva flow and all oral conditions analyzed (P>.05).Conclusion: The prevalence of oral diseases was similar in severely obese patients who were candidates for bariatric surgery and in patients who had been submitted to bariatric surgery. Nevertheless, there was higher prevalence of periodontal pockets in the operated group. (Eur J Dent 2012;6:191-197)
Keywords: Oral health; tooth erosion; periodontal diseases; dental caries; xerostomia; obesity; bariatric surgery